The Effectiveness of Speed Reading Technique in Improving Students’ Reading Comprehension at Fourth Semesters of English Department - Wahyudi, Mohammad Arief (Institut Agama Islam Negeri Kudus, 2018)
The purpose of the study is to know the effectiveness of Speed Reading Technique in improving the Reading Comprehension of the Fourth Semester students of English Department of STKIP PGRI Bangkalan. This study used Quantitative research. The result of reading speed was the experimental group higher than control group using posttest. The conclusion is the English Department students of STKIP PGRI Bangkalan could use Speed Reading Technique in improving reading comprehension.